A Critical thinking to build creative solutions - Fragata, Nuno (2020)
Introduction: The Learning Products for ALL (ProLearn4ALL) is a project which aims to make children aware of difference in the primary schools, with accessible multiform products, developed by higher education students. This process, which is founded on Problem Based Learning (PBL) methodologies, has as its main phases: the conceptualization of products and prototypes; pilot test; revision, reformulation and validation of products; and, finally the production and dissemination of a pedagogical kit. Objectives: The paper presents the PBL methodology as an active process used to develop critical thinking through the use of proposed prototype solutions to solve non-routine problems. Methods: Applying PBL methodology, the process started with the theoretical contextualization of the four main domains of disability (hearing, intellectual, motor, visual) and with the creation of prototypes, by students in the areas of Social Sciences and Education, to highlight the characteristics of each domain. Subsequently, Arts and Design students were asked to create playful and accessible products, based on the prototypes that were previously built. Results: Students were challenged to put themselves in the places of people with disability by using specific restrictions, created as thematic introductions to the proposed challenges. In this sense, the products were made with higher level of awareness, as students were simultaneously producers and users. Conclusion: The multiple reflections, during and after the production of the resources, allowed a constant process of research, validation and exclusion of solutions to occur, which progressively led to the construction of the final Pedagogical Kit.